The hidden face of ovarian cysts: a case of incidentally detected granulosa cell tumor - Kode, Siddhi A.; Pophalkar, Madhura; Kore, Siddhi S.; Kumari, Saroj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Adult granulosa cell tumors (AGCTs) are rare ovarian sex cord–stromal neoplasms that constitute 1–2% of ovarian malignancies and are often diagnosed late due to their nonspecific clinical, radiological, and biochemical features. We describe the case of a 50-year-old perimenopausal woman who presented with abnormal uterine bleeding and was found on ultrasound to have an endometrial polyp and a benign-appearing ovarian cyst, with normal tumor markers. She underwent laparoscopy-assisted vaginal hysterectomy with bilateral salpingo-oophorectomy, after which histopathological examination unexpectedly revealed an adult granulosa cell tumor in the left ovary, characterized by classic Call-Exner bodies and grooved (“coffee-bean”) nuclei. Immunohistochemistry demonstrated strong positivity for SF1 and Calretinin with focal Inhibin expression, confirming the diagnosis. The patient was staged as FIGO IA and placed on surveillance. This case highlights the importance of routine histopathological evaluation of adnexal masses even when preoperative findings appear benign, and underscores the need for long-term follow-up because AGCTs carry a risk of late recurrence.